Strategi Pengembangan Bisnis Dengan Metode Business Model Canvas - H Hartatik; Teguh Baroto (Department Industrial Engineering, University of Muhammadiyah Malang, 2017)
The company is required to continue to grow. This research uses Business Model Canvas method. Business Methods Canvas model is done with several stages of internal and external analysis using IFE and EFE matrix and SWOT Analysis. The next step is to weight using AHP method to get a strategy, then give variety with Canvas Business Model. The Canvas Business Model covers nine blocks, Customer Relationships, Key Partners, Value Propositions, Customer Segments, and cash flow, key resources (key resources), key activities (key activities) and cost structures (cost structures). The result of the research shows strategy with Business Model Canvas can effectively and efficiently in determining company strategy.